FSG band together to bust medical myths on a forum - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2019)
A forum was organized by the School of Chemistry and Environment on "Mitos Kesihatan di Media Sosial" on 28th February 2019 at Anjung Seri Budiman, UiTM Shah Alam. An overwhelmed count of 500 attendees from staff and students, including members of the public came to support the forum and was eager to seek its information to be shared on that day. Invited panels were Dr Sakinah Sulong, a medical doctor specialize in Family Medicine from the Ministry of Health Malaysia (KKM), Mr. Dziehan Mustafa, Senior Principal Assistant Director from National Pharmaceutical Regulatory Agency (NPRA) Malaysia, Dr Che Puteh Osman, a Felo from Atta-urRahman Institute for Natural Product Discovery, who is also a lecturer of Faculty of Applied Sciences, Universiti Teknologi MARA.